Boosting amoxicillin effectiveness against methicillin-resistant Staphylococcus aureus and ancomycin-resistant Enterococcus faecalis with phytochemicals: In vitro and in silico approaches - Pannapa Powthong, Nonthalert Lertnitikul, Cherdsak Boonyong (Journal of Applied Pharmaceutical Science, 2025)
Methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus faecalis (VRE) are one of the significant public health issues. They are associated with high rates of illness and death, and increased prevalence of antimicrobial resistance, which causes treatment failure in infectious diseases. This study investigated the effects of combined seven phytochemicals, including four stilbenoids [namely, pinosylvin monomethyl ether (1), 2,3’-dihydroxy-5’-methoxystilbene (2), (E)-2,3′-dihydroxy-2′-(4-hydroxybenzyl)-5′-methoxystilbene (3), (E)-2,5′-dihydroxy-2′-(4-hydroxybenzyl)-3′-methoxystilbene (4)], one flavonoid (isalpinin) (5), one triterpenoid saponin (oleanolic acid 28-O-β-D-glucopyranoside) (6), and one amide alkaloid (piperine) (7) with amoxicillin and predicting mode of action of seven natural compounds with amoxicillin to kill MRSA and VRE. The antibacterial activity was assessed by the minimum inhibitory concentration (MIC) and fractional inhibitory concentration (FIC) index. In addition, a molecular docking study was evaluated to predict the mechanism of action of their compounds to bind resistance-related proteins: penicillin-binding protein 2a (PBP2a) for MRSA and VanA ligase for VRE. All compounds showed antibacterial activity (MIC: 5–10 mg/ml) and enhanced amoxicillin efficacy, with FIC index values indicating additive to synergistic effects (FIC: 0.0018–0.8020). The compounds interacted with PBP2a at allosteric sites (ΔG: –11.70 to –6.60 kcal/mol; Ki: 0.00263–14.65 μM) and with VanA ligase at active sites (ΔG: –10.46 to –7.20 kcal/mol; Ki: 0.021–5.32 μM), exhibiting favourable binding affinities. In contrast, amoxicillin showed unfavourable interactions with these proteins. This study suggests that compounds 1–7 increased the susceptibility of MRSA and VRE to amoxicillin, which might be associated with their interaction with PBP2a and VanA proteins.
Keywords: Methicillin-resistant Staphylococcus aureus, vancomycin-resistant Enterococcus faecalis, antibacterial activity, penicillin-binding protein 2a, VanA ligase, amoxicillin, phytochemical